Recent Advances in Nanomaterials for Enhanced Colorimetric Detection of Viruses and Bacteria - Basso, Caroline R. [UNESP]; Filho, Marcos V. B. [UNESP]; Gavioli, Victoria D. [UNESP]; Parra, Joao P. R. L. L. [UNESP]; Castro, Gustavo R. [UNESP]; Pedrosa, Valber A. [UNESP] (MDPI, 2025)
The increasing prevalence of pathogen outbreaks underscores the urgent need for rapid, accurate, and cost-effective diagnostic tools. Colorimetric detection has gained significant attention among the available techniques due to its simplicity, portability, and potential for point-of-care applications. The nanomaterial-based colorimetric detection field continues to evolve, with innovations focusing on improving sensitivity, specificity, robustness, cost-effectiveness, and friendly analysis. Additionally, efforts to address limitations, such as stability and environmental impact, pave the way for more sustainable and reliable diagnostic solutions. This review highlights recent advances in nanomaterials for colorimetric pathogen detection in the last five years.
Keywords: aggregation; bacteria; gold nanoparticle; LFA; LSPR; virus